2017
DOI: 10.1002/jbt.22015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the interaction between proliferation, oxidant–antioxidant status, Wnt pathway, and apoptosis in zebrafish embryos exposed to silver nanoparticles used in textile industry

Abstract: Antimicrobial textile products are developing rapidly as an important part of functional textiles.Silver nanoparticles (AgNPs) are nanotechnology products with antimicrobial properties. However, exposure to nanoparticles in daily life is an important issue for public health, still being updated. Aim was to evaluate the effects of AgNPs on the development of zebrafish embryos focusing on Wnt pathway, proliferation, oxidant-antioxidant status, and apoptosis. The expressions of ccnd1 and gsk3 were determined by R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…In rodents, several kinds of metal-bearing NPs exhibit reproductive [29] and neurodevelopmental toxicities [30], probably due to oxidative stress, inflammation, or DNA damage [31]. Apoptosis induced by DNA damage and/or oxidative stress might be a mechanism underlying the developmental toxicity of SiO 2 NPs in zebrafish embryos, as shown in other studies on NP toxicity [32,33,34]. In addition, our results demonstrated that all types of SiO 2 NPs, regardless of the size or charges, were completely trapped by chorion, and subsequently blocked from exhibiting the toxicity to zebrafish embryos (Figure 5).…”
Section: Resultsmentioning
confidence: 95%
“…In rodents, several kinds of metal-bearing NPs exhibit reproductive [29] and neurodevelopmental toxicities [30], probably due to oxidative stress, inflammation, or DNA damage [31]. Apoptosis induced by DNA damage and/or oxidative stress might be a mechanism underlying the developmental toxicity of SiO 2 NPs in zebrafish embryos, as shown in other studies on NP toxicity [32,33,34]. In addition, our results demonstrated that all types of SiO 2 NPs, regardless of the size or charges, were completely trapped by chorion, and subsequently blocked from exhibiting the toxicity to zebrafish embryos (Figure 5).…”
Section: Resultsmentioning
confidence: 95%
“…Animals were kept in an aquarium rack system (Zebtec, Tecniplast, Italy) at 27 ± 1 °C under a light/dark cycle of 14/10 h. Animals were fed twice a day with commercial flake fish food complemented with live Artemia. All experiments were performed using reverse osmosis water supplemented with 0.018 mg L −1 Instant Ocean™ salt 42 . Since the embryos used were no older than 5 days old, Council of Europe (1986), Directive 86/609/EEC or the Marmara University ethics committee did not require license.…”
Section: Methodsmentioning
confidence: 99%
“…The net absorbance was calculated by measuring absorbances at 0 and 8 th minutes of illumination. The results were expressed as U/mg protein 42,50 .…”
Section: Methodsmentioning
confidence: 99%
“…Based on the above properties, herein, AO was adopted to stain the zebrafish larvae treated with PNCHO-b-PNTEG at different concentrations and images analyze were carried out employed Image J for quantifying the fluorescence intensity, and the toxicity of this polymeric carrier was thus evaluated from the level of cell death. In the control group (Figure 10(a)), weak green fluorescence is significantly observed at the yolk sac of zebrafish larva after 96 hpf, which is attributed to the voluntary and orderly apoptosis controlled by genes [35,36]. Unlike the cell necrosis under pathological conditions, cell apoptosis, involving the activation, expression, and regulation of a series of genes, is an active death process to better adapt to the living environment [28].…”
Section: Cell Death In Live Zebrafishmentioning
confidence: 99%
“…As a nucleic acid selective fluorescent dye, AO has the ability to penetrate into apoptotic or necrotic cells and further combine with intracellular DNA or RNA molecules [35,36]. Bright green fluorescence could be observed for the combination of AO with DNA, while for the combination with RNA, orange-red or fire-red could be found.…”
Section: Cell Death In Live Zebrafishmentioning
confidence: 99%